2017
DOI: 10.1177/0022022117701194
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Culture and Identity on Emotional Reactions to Insults

Abstract: People from honor cultures show heightened emotional responses to insults to their social image. The current research investigates whether people from honor cultures also show heightened protection of social identities. We find that honor concerns may be embedded in some social identities but not others, and that those identities associated with honor concerns are defended more than identities not associated with honor. Three experiments investigated participants' emotional responses to insults to their ethnic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 42 publications
2
32
0
Order By: Relevance
“…Travaglino et al's (2014) findings suggested that honour is an important concern in southern Italy. Yet, those same cultural values and norms may become less relevant vis-à-vis other groups to which individuals also belong (Maitner, Mackie, Pauketat, & Smith, 2017; Rodriguez Mosquera, 2016).…”
Section: Social Identity Regional Membership and Opposition To Criminalmentioning
confidence: 99%
“…Travaglino et al's (2014) findings suggested that honour is an important concern in southern Italy. Yet, those same cultural values and norms may become less relevant vis-à-vis other groups to which individuals also belong (Maitner, Mackie, Pauketat, & Smith, 2017; Rodriguez Mosquera, 2016).…”
Section: Social Identity Regional Membership and Opposition To Criminalmentioning
confidence: 99%
“…Second, this is the first study in cultures of honour research that utilizes appraisal theory by examining the path from appraisals to action readiness through emotions. A few studies that focused on appraisal theory primarily compared each component separately across different cultures (appraisals, emotions, and action readiness) rather than examining the relations among them (Maitner, Mackie, Pauketat, & Smith, 2017;Mesquita, 2001;Rodriguez Mosquera et al, 2000), or they examined the mediating role of motivations (e.g., motivation to punish the offender) between emotions and behaviours, without including the appraisal of the situation in their model as an antecedent of emotions (Rodriguez Mosquera et al, 2008). Finally, this is the first study that examines helplessness as a response to reputation threats.…”
Section: The Present Researchmentioning
confidence: 99%
“…Next, we examined whether participants' emotional responses (anger & shame) mediated the relation between appraisal of threats (humiliating & rude) and helplessness. We estimated the direct and indirect effects using bootstrap sampling (5000 resamples; Shrout & Bolger, 2002) on MPlus Version 8 (Muthén & Muthén, 1998-2017; see Figure 1). Turkey.…”
Section: Path Analysesmentioning
confidence: 99%
“…Notably, the studies reported here were carried out in four educational jurisdictions (Canada, Croatia, France and the United States), and provided primary and secondary data from teachers and students at different ages. Research has shown that different cultures ascribe different values to conformity to social norms, commitment to group work and tolerance of differences, which might affect respondents' interpersonal relationships and subjective wellbeing (Chiu & Chow, 2011;Maitner, Mackie, Pauketat, & Smith, 2017). Given these cross-cultural differences, while readers need to take caution in generalising the findings to other cultures, the studies reported here do provide a strong foundation for extending the research to other cultural settings.…”
Section: Social and Emotional Learningmentioning
confidence: 77%